Anita Rákóczy, Mariko Hori Tanaka, and Nicholas E. Johnson, eds. Influencing Beckett / Beckett Influencing - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2022)
Although Beckett is a highly acclaimed author in Hungary whose works are available in translation, and his plays have been staged several times since the Hungarian premiere of Waiting for Godot in 1965, books written about him by Hungarian authors were unduly delayed. This strange, long-standing situation became luckily altered by the publication of the essay collection under review here in 2020. The essays were originally papers given at the Samuel Beckett Working Group meeting held at Károli Gáspár University of the Reformed Church in Budapest, organized by the three scholars who edited the collection. The preface to the book is written by renowned Beckett scholar Linda Ben-Zvi, also one of the organizers as representative of IFTR, the International Federation for Theatre Research, “the largest theatre organization in the world.” The Beckett Working Group of the organization had its first meeting in Tel Aviv in 1996, and in 2017 it was hosted by Károli Gáspár University of Budapest. From the start, Ben-Zvi emphasizes, discussions have been enlivened by the diverse cultural experiences of the international mix of group members, ranging from PhD students to professors (9). In accordance, the authors of the present essay collection are from several countries, including Hungary.